2009
DOI: 10.1016/j.chembiol.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Interaction Kinetics of the Pheromone- Binding Protein from the Gypsy Moth, L. dispar: Insights into the Mechanism of Binding and Release

Abstract: The pheromone-binding proteins (PBPs), which exist at a high concentration in the sensillum lymph surrounding olfactory neurons, are proposed to be important in pheromone detection and discrimination in insects. Here, we present a systematic study of PBP-ligand interaction kinetics. We find that PBP2, from the gypsy moth, Lymantria dispar, associates and dissociates slowly with its biofunctional ligands, (+)- and (-)-disparlure. Tryptophan anisotropy measurements detect PBP multimers in solution as well as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 42 publications
6
71
0
1
Order By: Relevance
“…These findings may be due to the abnormal kinetics of these OBP-ligand mixtures. For some OBP-ligand interactions, 5 min may be insufficient time to establish an equilibrium (Gong et al 2009a). The mathematical treatment that was used to extract K i values assumed that: 1) the ligand and probe compete for one binding site and 2) the three partners (competing ligand, 1-NPN and PBP) reach equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be due to the abnormal kinetics of these OBP-ligand mixtures. For some OBP-ligand interactions, 5 min may be insufficient time to establish an equilibrium (Gong et al 2009a). The mathematical treatment that was used to extract K i values assumed that: 1) the ligand and probe compete for one binding site and 2) the three partners (competing ligand, 1-NPN and PBP) reach equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Independent models were proposed for the biological role of each OBP in chemosensation. A pheromone-binding protein (PBP) of the gypsy moth Lymantria dispar , PBP2, is thought to function as a scavenger [12], [13]. Another PBP in the silkworm moth Bombyx mori , PBP1, is considered as a transporter for the ligand, bombykol [14].…”
Section: Introductionmentioning
confidence: 99%
“…The dendritic membrane (8) houses the olfactory receptors (7) and the sensory neuron membrane protein (6). The figure is from Gong et al, 9 reproduced with kind permission of Chemistry & Biology, © 2009 Elsevier. added to the organic phase using a 10 µL glass syringe from a 50 mg mL -1 stock solution in distilled n-hexane.…”
Section: Determination Of Partition Coefficientsmentioning
confidence: 98%
“…Experimental studies of these interactions and their kinetics have recently been reported. 9 Further insight could be achieved through molecular modeling and molecular dynamics (MD) simulations. With recent advances in computer technology, MD has become an excellent companion and a viable alternative to often costly and difficult experiments.…”
Section: Introductionmentioning
confidence: 99%